Integrated framework of traffic characterization and performance analysis for Universiti Network [electronic resource] - Mazleena Salleh 333705 (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Ph.D (Sains komputer)) - Universiti Teknologi Malaysia, 2007